Resilience of the university teacher as an organizational strategy in the context of transdisciplinarity (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
The purpose of the research was to evaluate the action of the university professor based on resilience as an organizational strategy in a transdisciplinary context. The predominant paradigm in the study is quantitative, under a field design, descriptive and holistic. The theoretical foundations were addressed: Must Be of Teaching Action - Positive Resilient Argument; Knowing and Doing Teaching - Resilient Positive Reticulation, Teaching based on Resilience, Resilience of the teacher as an organizational strategy and Teaching resilience in the context of transdisciplinarity, this served as an interpretive framework for the findings obtained. The methodological procedure was derived from the answers given by 43 teachers from the Dean of Economic and Business Sciences (DCEE) of the Centroccidental University "Lisandro Alvarado" (UCLA). The agglutination of the behavior of the data was carried out through a questionnaire on a Likert scale. The results determined that the University should promote the application of teaching strategies based on Resilience to help increase educational quality, through institutional self-evaluation, the construction of knowledge and pedagogical, scientific, ethical and humanistic that promotes the student obtaining new knowledge and progress in their educational development. It is concluded that the reconstruction of the teaching action is required in the face of the vicissitudes of the complex university world, capable of considering the distinctions and realities that are alternative to each other, removing the transdisciplinary background for a high level of result in their educational praxis and in the conduction of the teaching
Keywords: resilient teacher; organizational strategy; transdisciplinary context